Alleviating Poverty in Nigeria through Islamic Strategies - Sambo, Usman; Sule, Babayo; Zamfara, Misbahu Ibrahim (FISIP UIN Sunan Gunung Djati Bandung, 2025)
Research Problem: Poverty in Nigeria is widespread and deeply entrenched, affecting the majority of the population. This persistent deprivation is exacerbated by policy failures, corruption, and the limited adoption of alternative poverty‐alleviation strategies. Recent reports indicate a rapid rise in multidimensional poverty, pushing many households into extreme hardship and making day-to-day survival increasingly difficult. Research Purposes: This study aims to analyze poverty-alleviation strategies through an alternative Islamic approach, assess the potential of Islamic instruments to reduce inequality and poverty in Nigeria, and formulate recommendations for integrating these mechanisms into government policies and programs. Research Methods: The research employs a qualitative design, drawing data from existing documents and secondary sources. Analysis is grounded in empiricism, involving rigorous evaluation of prior studies to test their validity and accuracy and to ensure that conclusions rest on a robust evidence base. Results and Discussion: Findings show that Islamic teachings—derived from Qur’anic verses, prophetic traditions, and scholarly consensus—offer credible mechanisms to address poverty. Core instruments include zakat, inheritance, charity (sadaqah), gifts (hibah), feeding initiatives, and selfless community support. These mechanisms mobilize wealth from the affluent and redistribute it to the less privileged, thereby narrowing inequality and lowering poverty levels; however, their potential impact in Nigeria remains underrealized due to weak implementation, policy shortcomings, and corruption. Research Implications and Contributions: At the policy level, governments should intensify zakat collection and other organized forms of charity and establish capable agencies to redistribute resources fairly and effectively. Practically, the study offers an actionable framework for integrating Islamic social-finance tools into poverty-reduction programs. Academically, it consolidates evidence that Islamic economic instruments constitute context-appropriate and credible strategies for reducing poverty and inequality in Nigeria.